Les soins médicaux de jeunes hommes et de jeunes femmes qui décèdent par suicide. (March 2018) - Rhodes, Anne E.; Boyle, Michael H.; Bridge, Jeffrey A.; Sinyor, Mark; Katz, Laurence Y.; Bennett, Kathryn; Newton, Amanda S.; Links, Paul S.; Tonmyr, Lil; Skinner, Robin; Cheung, Amy; Bethell, Jennifer; et al.
Objective: Prior year medical care was compared among youth dying by suicide to their peers. Effect modification of these associations by age or place of residency (rural versus larger community sizes) was examined in a large, medically insured population. Method: This population-based case control study used data from the Office of the Chief Coroner in Ontario, Canada, linked to health care administrative data to examine associations between medical care for mental health or other reasons (versus no medical care) and suicide. Decedents ( n = 1203 males and n = 454 females) were youth (aged 10 to 25 years) who died by suicide in Ontario between April 2003 and March 2014, inclusive. Peers of the same ages were frequency matched to decedents on sex and place of residency. Logistic regression was used to calculate odds ratios and 95% confidence intervals and to test effect modification. Results: Associations with mental health care were stronger in decedents than peers with a gradation of care (i.e., outpatient only, emergency department [ED], inpatient care) in both sexes. However, these associations were weaker among youth living in rural communities. Furthermore, older males (aged 18 to 25 years) were less likely than younger males (aged 10 to 17 years) to access the ED (ambulatory care only). This decrease was observed in rural and larger communities alongside no increase in medical care for other reasons. Conclusions: Geographical and age-related barriers to mental health care exist for youth who die by suicide. Preventive efforts can address these barriers, intervening early and integrating services, including the ED.